The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12876-018-0837-4
|View full text |Cite
|
Sign up to set email alerts
|

What is impact of nonsteroidal anti-inflammatory drugs in the prevention of post-endoscopic retrograde cholangiopancreatography pancreatitis: a meta-analysis of randomized controlled trials

Abstract: BackgroundRecently, although studies have investigated the role of NSAIDs in the prevention of post-endoscopic retrograde cholangiopancreatography pancreatitis (PEP), selection of the ideal drug, the time and route of its administration for the appropriate population remain controversial.MethodsA systematic search was done in sources including PubMed, Embase, Web of Science, the Cochrane Library Central, and ClinicalTrials.gov from from August 1, 1990 to August 1, 2017. Randomized controlled trials comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 51 publications
1
27
0
4
Order By: Relevance
“…The RCT by Levenick et al that did not demonstrate a beneficial effect of NSAIDs in consecutive patients undergoing ERCP [88] has received many comments and criticisms. Four of the most recent meta-analyses confirmed that this study is an outlier among the RCTs that assessed the effect of NSAIDs in patients at average risk for PEP [79,80,89,90]. Therefore, also considering logistical reasons as well as the benefit of pre-ERCP as compared with post-ERCP administration of NSAIDs (see below), and the fact that patients may become at high risk for PEP during ERCP, we recommend routine administration of NSAIDs.…”
Section: Recommendationmentioning
confidence: 80%
“…The RCT by Levenick et al that did not demonstrate a beneficial effect of NSAIDs in consecutive patients undergoing ERCP [88] has received many comments and criticisms. Four of the most recent meta-analyses confirmed that this study is an outlier among the RCTs that assessed the effect of NSAIDs in patients at average risk for PEP [79,80,89,90]. Therefore, also considering logistical reasons as well as the benefit of pre-ERCP as compared with post-ERCP administration of NSAIDs (see below), and the fact that patients may become at high risk for PEP during ERCP, we recommend routine administration of NSAIDs.…”
Section: Recommendationmentioning
confidence: 80%
“…On occasion, an urgent ERP may need to done to place a pancreatic stent or replace a migrated stent in an attempt to modify the course of an evolving PEP and hasten recovery[109]. Peri-procedure rectal indomethacin 100 mg[110, 111, 112, 113] and post procedure intravenous lactated Ringer’s solution[114] have also been shown to reduce the risk of PEP.…”
Section: Managementmentioning
confidence: 99%
“…In recent years, rectal NSAIDs were proved to be effective in average-risk and high-risk patients. [ 28 , 29 ] Rectal NSAIDs are cheap and of low risk. Meta-analyses showed that the overall rates of adverse events in the NSAIDs groups versus control groups were found no significant difference, as well as the specific complications such as gastrointestinal bleeding, renal dysfunctions and anal itching.…”
Section: Discussionmentioning
confidence: 99%